River boy - Bowler, Tim. (Oxford : Oxford University Press, 2001)
Knowing that he is dying, Jess's grandfather insists on returning to the river he had known as a boy to finish a special painting and fulfill a life-long dream.
5.2
5-8.
5-8
Keywords: Artists -- Fiction; Death -- Fiction; Grandfathers -- Fiction; Swimming -- Fiction; Artists -- Fiction; Death -- Fiction; Grandfathers -- Fiction; Swimming -- Fiction